Well-defined, Reversible Disulfide Cross-linked Micelles for On-demand Paclitaxel Delivery - Li, Yuanpei (2011)
To minimize premature release of drugs from their carriers during circulation in the blood stream, we have recently developed reversible disulfide cross-linked micelles (DCMs) that can be triggered to release drug at the tumor site or in cancer cells. We designed and synthesized thiolated linear-dendritic polymers (telodendrimers) by introducing cysteines to the dendritic oligo-lysine backbone of our previously reported telodendrimers comprised of linear polyethylene glycol (PEG) and a dendritic cluster of cholic acids. Reversibly cross-linked micelles were then prepared by the oxidization of thiol groups to disulfide bond in the core of micelles after the self-assembly of thiolated telodendrimers. The DCMs were spherical with a uniform size of 28 nm, and were able to load paclitaxel (PTX) in the core with superior loading capacity up to 35.5% (w/w, drug/micelle). Cross-linking of the micelles within the core reduced their apparent critical micelle concentration and greatly enhanced their stability in non-reductive physiological conditions as well as severe micelle-disrupting conditions. The release of PTX from the DCMs was significantly slower than that from non-cross-linked micelles (NCMs), but can be gradually facilitated by increasing the concentration of reducing agent (glutathione) to an intracellular reductive level. The DCMs demonstrated a longer in vivo blood circulation time, less hemolytic activities, and superior toxicity profiles in nude mice, when compared to NCMs. DCMs were found to be able to preferentially accumulate at the tumor site in nude mice bearing SKOV-3 ovarian cancer xenograft. We also demonstrated that the disulfide cross-linked micellar formulation of PTX (PTX-DCMs) was more efficacious than both free drug and the non-cross-linked formulation of PTX at equivalent doses of PTX in the ovarian cancer xenograft mouse model. The anti-tumor effect of PTX-DCMs can be further enhanced by triggering the release of PTX on-demand by the administration of the FDA approved reducing agent, N-acetylcysteine, after PTX-DCMs have reached the tumor site.